Front Office Department Service Quality during the Covid-19 Period - Ni Made Ayu Safitri; I Nyoman Rajin Aryana; Ida Ayu Elistyawati; Made Sudiarta; Ni Luh Eka Armoni (International Journal of Travel, Hospitality and Events, 2022)
ABSTRACT Purpose: This study was to determine the service quality of the front office department and the efforts of the front office department in Canggu Dream Village, Bali, Indonesia, to maintain and improve the quality of the services given. Research methods: This study used descriptive statistical analysis techniques with 90 samples of guest reviews selected using purposive sampling method. The source of data is guest reviews for one year from January 2020 to December 2020 on online travel agents. Results and discussion: There were comparisons of positive reviews with a total of 94% while negative reviews are only 6%. Each variable gets a different percentage, the empathy variable gets a percentage of 50% and becomes the most dominant variable in positive reviews. Implication: All the variables have a higher percentage of positive reviews than negative reviews. Keywords: quality of service, guest complaints, front office department.